Pemberdayaan UMKM Berbasis Digital melalui Penguatan Strategi Pemasaran, Literasi Keuangan, dan Ketahanan Ekonomi Lokal - Erick Karunia; Muh.Irfandy Azis; Mohamad Nur Utomo; Shalahuddin Shalahuddin; Deni Marsha; Aswan Aswan; Olivia Pamilangan Andilolo; Nursia Nursia; Suryaningsih Suryaningsih; Adhy Satya Pratama (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service program aims to empower Micro, Small, and Medium Enterprises (MSMEs) in Tarakan City, North Kalimantan, by enhancing their capacity in digital marketing strategies, financial literacy, and strengthening local economic resilience. The program was implemented using a participatory and practical approach through a series of activities including needs assessment, integrated training, workshops, and direct mentoring for MSMEs actors. The results indicate a significant improvement in participants' skills, particularly in utilizing social media and marketplaces for product promotion, maintaining basic financial records using digital applications, and conducting structured financial planning for their businesses. Furthermore, this initiative successfully fostered a shift in mindset—from traditional business management toward more strategic and data-driven decision-making. The success of this program demonstrates that well-targeted educational interventions can enhance the competitiveness of UMKM, especially in the face of digital transformation and economic uncertainty. However, sustainable impact requires ongoing assistance and multi-stakeholder collaboration. This program is expected to serve as a replicable model for similar initiatives in other regions.